Characteristics of registration of medical records in a hospital in southern Peru - Quispe-Juli, Cender Udai (2016)
Objective: To determine the characteristics of registration of medical records of hospitalization in the Hospital III Yanahuara in Arequipa, Peru. Material and methods: The study was observational, cross-sectional and retrospective. 225 medical records of hospitalization were evaluated in November 2015. A tab consisting of 15 items was used; each item was assessed using a scale: "very bad", "bad", "acceptable", "good" and "very good". Adescriptive analysis was done by calculating frequency. Results: Items with a higher proportion of acceptable registration data were: clear therapeutic indication (84%), clinical evolution (74.7%), diagnosis (70.7%), complete and orderly therapeutic indication (54.2%), medical history taking (50.2%) and physical examination (43.1%). The very well recorded items were: indication of tests and procedures (97.3%), medical identification (91.1%) and allergies (67.1%). Very bad recorded items were: reason for admission (91.1%), life habits (72.9%) and prior treatment (38.2%). Conclusions: Most medical records of hospitalization are characterized by an acceptable record of most evaluated items; however they have notable deficiencies in some items.